Rodin, Vigeland and the Middle Ages - Marthje Sagewitz (Kunst og Kultur)
In his search for an effective form for his famous Burghers of Calais (1884–1895), Auguste Rodin seems to have looked at medieval models. The emotional expressiveness of medieval sculpture also inspired Gustav Vigeland who refers in his early works to Rodin’s Burghers in “medieval dress”. This article aims to compare Vigeland’s references to medieval art with those of Rodin and to examine their recourse to the art of the Middle Ages in the socio-political and historical context of their time.